Comparison of accuracy of panoramic radiograph and lateral cephalogram in determining linear mandibular measurements among orthodontic patients in tertiary dental care center of Kathmandu - Piya, Anshu; Shrestha, Bikash Veer; Khapung, Anju; Bhattarai, Prakash (Nepal Medical College Journal, 2023)
Mandibular dimensions are one of the key parameters for planning the treatment by an Orthodontist. Lateral cephalograms are usually used to evaluate the skeletal relationship. However, due to the superimposition of both the sides, lateral cephalogram may not be reliable in measuring the right and left sides of the cranial landmarks. Panoramic radiography delivers a wide-ranging view of maxillofacial structures with comparatively lesser radiation exposure than other tools and superimposition of structures is less compared to lateral cephalogram image. OPG and lateral cephalograms of all the patients of age group 16-35 years attending Department of Orthodontics in Nepal Medical College from September 2022 to February 2023, having Angle’s Class I Molar relationship with minimum crowding was taken. Linear measurements (ramus height, total mandibular length and mandibular body length) were measured on OPG and Lateral cephalogram. The data was processed in SPSS version 17 for further analysis. There was no statistically significant difference in mean linear measurements between right and left sides on OPG (p-value 0.77, 0.49 and 0.59 respectively). But there was a statistically significant difference in mean linear measurements between both sides on OPG and lateral cephalograms (p-value <0.001). OPG can be used reliably to measure the mandibular length and ramus height of right and left side but comparison of mandibular length and ramus height between lateral cephalogram and OPG may not be reliable.